2014
DOI: 10.1111/opn.12057
|View full text |Cite
|
Sign up to set email alerts
|

Competence in advanced older people nursing: development of ‘Nursing older people – Competence evaluation tool’

Abstract: Those who nurse older people require competence that is complex and comprehensive. One way to evaluate nursing competence is through evaluation tools such as the Nursing Older People--Competence Evaluation tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 31 publications
1
72
0
10
Order By: Relevance
“…However, the results correlate well with Norwegian and international studies on patient safety, medication use and competence needs in nursing homes (6,8,11,15,16,18,(20)(21)(22).…”
Section: Implications For Education and Practicesupporting
confidence: 79%
See 2 more Smart Citations
“…However, the results correlate well with Norwegian and international studies on patient safety, medication use and competence needs in nursing homes (6,8,11,15,16,18,(20)(21)(22).…”
Section: Implications For Education and Practicesupporting
confidence: 79%
“…Professional identity must be boosted, and the role of the nurse shielded from tasks that do not require nursing competence (6). Internal control in nursing homes must be improved.…”
Section: Implications For Education and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…(Cummings and Bennett, 2012: 13) Competence is a commonly used term in nursing and is frequently interpreted as being about a skilled performance (Garside and Nhemachena, 2013;Bing-Jonsson et al, 2015). Similarly, in Benner's (1984) seminal work 'Novice to expert', competent nurses were able to carry out conscious and deliberate planning and prioritise and manage their work, but without the flexibility and speed of proficient nurses.…”
Section: 'Competence Means All Those In Caring Roles Must Have the Abmentioning
confidence: 99%
“…If a skilled, evidence based performance is not accompanied by an appropriate attitude, such as respect and a non-discriminatory approach, the care experience is likely to be undignified. In a study of competencies required to care for older people, the wide range identified included communication (Bing-Jonsson et al, 2015), which is another of the 6Cs. Competence should also include cultural competence, with nurses providing care in a culturally appropriate manner for each person and their family.…”
Section: 'Competence Means All Those In Caring Roles Must Have the Abmentioning
confidence: 99%